Mixed eco-neighborhood: Matsaria as a model of post-industrial transformation - Garcia Odiaga, Iñigo; Azpiazu Lejardi, Nekane; Gual Ors, Francisca (Frontiers in Sustainable Cities, 2025)
The research shows how a disused industrial fabric can be transformed to adapt to emerging urgencies. As urban environments evolve, the regeneration of abandoned areas becomes an opportunity to rethink traditional urban planning models. In contrast to the city structured in specialized bodies, the study analyzes a more flexible and dynamic model, where spaces allow to assume changes, and thus function in a resilient manner. Through an inductive methodology based on the analysis of significant case studies, such as The New Urban Fabrik: Torrent Estadella eco-industrial park, it concludes in a decalogue of strategies applicable in urban centers, which delves into the reuse of buildings and hybridization of uses, as well as the implementation of solutions focused from a more-than-human vision in public space to promote multi-species cohabitation. These guidelines arise from common patterns detected in successful processes of urban and industrial regeneration, demonstrating their capacity for transformation in non-specialized structures. The result of the research, is the image of a new urban model in the post-industrial area Matsaria of Eibar, which is obtained through the implementation of the guidelines of the decalogue. The intervention shows its transformation towards a sustainable hybrid infrastructure based on post-natural ecological design. The study highlights the conversion capacity of urban fabrics that became obsolete due to the zonification of uses, and how they can be converted into inclusive and versatile spaces that ensure greater integration between economic, social and cultural activities. The decalogue not only serves as a practical guide for interventions in similar industrial environments, but also opens the way for reflection on its possible application in any urban fabric, inspiring a new vision for the city model of the future based on the capacity for constant adaptation.